Safety risk control in construction engineering based on the interval analytic hierarchy process and technique for order preference by similarity to ideal solution. Issue 4 (15th November 2021) - Du, Minggang; Han, Tongyin; Shang, Yanliang
Abstract: To improve the safety management level of construction projects, the housing construction project was taken as the research object and the hierarchical structure model by using the improved analytic hierarchy process (IAHP) was established. Based on the four dimensions of human, material, environment, management, the 12 influencing factor evaluation indexes and 34 scoring items were designed. By the redistribution of weight, the value range of scoring items was determined, and then the construction safety management evaluation system was constructed to evaluate the project safety management. When evaluating multiple projects, if the overall evaluation conclusion is poor, the technique for order preference by similarity to an ideal solution (TOPSIS) was used to evaluate the relative advantages and disadvantages of the project by introducing reference interval α [0.5, 0.6]. By calculating the membership relationship between nearness degree L i + and reference interval α, the decision‐making method to improve the level of project safety management was given. The results show that, if L i + > 0.6, need external interactive learning, if L i + < 0.5, internal communication and learning can be organized. If L i + ∈ α, the project safety management level can be improved by the combination of external interactive learning and internal experience exchange. Abstract : Based on the improved analytic hierarchy process (IAHP) and TOPSIS method, the construction project safety evaluation index system is constructed to evaluate the safety management of the construction project in the construction stage. Under the general evaluation, it provides a basis for improving the safety management level and decision‐making methods.